DEGRADATION OF SOME PESTICIDES IN THE FIELD AND EFFECT OF PROCESSING - CELIK, S; KUNC, S; ASAN, T (Royal Soc Chemistry, 1995)
Standard methods have been applied for the analysis of pesticides, namely diazinon, azinphos-methyl, pirimicarb, methidathion, ethion and phosalone, used most frequently in the Elazig region. In order to find out the rates of degradation of pesticides on vegetables and fruit, the residues were analysed under native field conditions over a period of time. The effects of washing and peeling on the pesticide residue levels in fruits and vegetables were investigated. In addition, the effects of sunlight, volatilization and micro-organisms on the disappearance and fate of pesticide residues in the products were also studied in relation to time.
Keywords: AZINPHOS-METHYL; DIAZINON; ETHION; PIRIMICARB; METHIDATHION; PHOSALONE; VOLATILIZATION; SUNLIGHT; DECOMPOSITION; BIOLOGICAL DEGRADATION